The effectiveness of organic pollutants removal in constructed wetland with horizontal sub-surface flow = Efektywność usuwania zanieczyszczeń organicznych w oczyszczalni hydrofitowej - Jakubaszek, Anita; Sadecka, Zofia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the results of the research work related to the removal efficiency from wastewater organic pollutants and suspended solids at HSSF (horizontal subsurface flow) construcred wetland. The average effectiveness defined as loss of value COD in wastewater has reached 77%, for BOD5- 80% and TOC - 82%.
Keywords: oczyszczanie ścieków; oczyszczalnie hydrofitowe; wastewater treatment; constructed wetlands